Identification and determination of the prevalence of gastrointestinal parasites in children ages 2-5 years old in Barangay 239 and Barangay 154 Tondo, Manila - Mata, Cecille P. 4 0 16; 5 (2005)
u
Thesis: (B.S. Biology)-Pamantasan ng Lungsod ng Maynila, 2005.
Keywords: 2 -- 0; 6; 20; 20; 2